Concomitant elevations of MMP‐9, NGAL, proMMP‐9/NGAL and neutrophil elastase in serum of smokers with chronic obstructive pulmonary disease. Issue 7 (22nd December 2016) - Bchir, Sarra; Nasr, Hela ben; Bouchet, Sandrine; Benzarti, Mohamed; Garrouch, Abdelhamid; Tabka, Zouhair; Susin, Santos; Chahed, Karim; Bauvois, Brigitte
Abstract: A growing body of evidence points towards smoking‐related phenotypic differences in chronic obstructive pulmonary disease (COPD). As COPD is associated with systemic inflammation, we determined whether smoking status is related to serum levels of matrix metalloproteinase‐9 (pro‐ and active MMP‐9), neutrophil gelatinase‐associated lipocalin (NGAL) and the proMMP‐9/NGAL complex in patients with COPD. Serum samples were collected in 100 stable‐phase COPD patients (82 smokers, 18 never‐smokers) and 28 healthy adults (21 smokers, 7 never‐smokers). Serum levels of studied factors were measured in ELISA. Our data provide the first evidence of simultaneously elevated serum levels of MMP‐9, NGAL and proMMP‐9/NGAL in COPD smokers. While the triad discriminated between smokers and non‐smokers in the COPD group, MMP‐9 and proMMP‐9/NGAL (but not NGAL) discriminated between smokers with and without COPD. Adjustment for age and smoking pack‐years did not alter the findings. Serum MMP‐9, NGAL and proMMP‐9/NGAL levels were not correlated with the GOLD stage or FEV1 decline. Furthermore, serum levels of neutrophil elastase (NE) and MMP‐3 (but not of IL‐6 and MMP‐12) were also higher in COPD smokers than in healthy smokers before and after adjustment for age and pack‐years. Among COPD smokers, levels of MMP‐9, NGAL and proMMP‐9/NGAL were positively correlated with NE ( P < 0.0001) but not with the remaining factors. Gelatin zymography detected proMMP‐9 in serum samples of healthy and COPD smoking groups. Our results suggest that associated serum levels of proMMP‐9, NGAL, proMMP‐9/NGAL and NE may reflect the state of systemic inflammation in COPD related to cigarette smoking.